Animal models of portal hypertension - Abraldes, Juan G (Baishideng Publishing Group Co., Limited, 2006)
Animal models have allowed detailed study of hemodynamic alterations typical of portal hypertension and the molecular mechanisms involved in abnormalities in splanchnic and systemic circulation associated with this syndrome. Models of prehepatic portal hypertension can be used to study alterations in the splanchnic circulation and the pathophysiology of the hyperdynamic circulation. Models of cirrhosis allow study of the alterations in intrahepatic microcirculation that lead to increased resistance to portal flow. This review summarizes the currently available literature on animal models of portal hypertension and analyzes their relative utility. The criteria for choosing a particular model, depending on the specific objectives of the study, are also discussed.